Utilização de insertos de cerâmica no torneamento de desbaste da liga de níquel 625 depositada em forma de revestimento metálico - Krebs, Gabriel (2019)
The use of nickel alloys is imperative to the industries that manufacture submarine equipment for the Oil and Gas industry, which due to corrosive characteristics, high temperatures, high pressures and the combinations of these factors existent in an extremely adverse environment, must be high resistant to corrosion and have excellent mechanical properties. One of the characteristics of nickel based alloys is the poor machinability, which results in the use of low cutting speeds, thus making the whole process more expensive. In addition, the high costs related to the acquisition of this material require the adoption of alternatives, such as the application of overlay using nickel alloy625 over carbon steel parts. Different studies have been carried out inconel 718 alloy machining, which has been proved to have wide use. However, the literature about machining the nickel alloy 625, especially on the overlay form, is limited. In this work the use of ceramic inserts (Al2O3 + SiCw and SiAlON) for the rough turning of overlay of nickel alloy 625 on the AISI 4130 steel, by means of the automatic TIG process, considering the tool life and the quality of the machined surface is being analyzed. Initially experiments were carried out to define the class of the insert and the appropriate cutting parameters. Later, the tool life, surface and sub-surface characteristics of the machined surface were examined, such as microhardness, work-hardening and surface finish for different conditions of coolant and insert diameter. The results obtained show that the surface characteristics of the overlay have direct interference on the grade definition of the insert to be used, although it is not able to change the wear mechanism on the tool edge. The use of coolant means has also been proved essential for the machining to be performed under satisfactory conditions.